KONTRIBUSI PENGUASAAN QAWAID AN-NAHWIYAH TERHADAP PEMAHAMAN TEKS KITAB KUNING PADA SANTRI KELAS 1A ULYA DI PONDOK PESANTREN RAUDHATUT THALIBIN - Radiatun Nazwa; Darul Kutni; Laksana Tri Prasetya (STIT Darul Hijrah Martapura, 2025)
This study aims to determine the contribution of qawaid an-nahwiyah mastery to the comprehension of kitab kuning texts among first-year Ulya students at Pondok Pesantren Raudhatut Thalibin. Mastery of nahwu (Arabic grammar) serves as a fundamental foundation for understanding the structure and meaning of classical Arabic texts, especially kitab kuning, which are typically written without diacritical marks. Students are expected not only to read the texts but also to understand their content and sentence structures accurately. This research employs a quantitative approach with an associative correlational method. Data were collected through tests measuring students' mastery of qawaid an-nahwiyah and their comprehension of kitab kuning texts. The sample consisted of 25 students. Data analysis was carried out using simple linear regression. The findings reveal a strong and statistically significant relationship between qawaid an-nahwiyah mastery and kitab kuning comprehension (R = 0.937; R² = 0.876; p < 0.05). The coefficient of determination indicates that 87.6% of the variation in text comprehension can be explained by qawaid an-nahwiyah mastery, while 12.4% is associated with factors outside the regression model. These findings indicate that higher mastery of Arabic grammar is associated with better comprehension of classical Islamic texts.